Eosinophil density in common benign and malignant salivary gland tumors with congo red staining - Safoura Seifi; Zahra Azizi; Alten Ghanghermeh; Shahriar Eftekharian; Jahanshah Salehinejad; Hemmat Gholinia (Indian Journal of Medical and Paediatric Oncology)
Purpose: Eosinophils are multifunctional leukocytes with unknown mechanisms in salivary gland tumors. Some researchers associate eosinophils with tumor progression and others have proposed them as antitumoral. The present study was conducted to compare the density of eosinophils in common salivary gland tumors and its relationship with the degree of differentiation in malignant salivary gland tumors. Materials and Methods: In this present descriptive-analytical, cross-sectional study, 15 cases of pleomorphic adenoma, 15 cases of adenoid cystic carcinoma (ACC), 30 cases of mucoepidermoid carcinoma (MEC), and 5 cases of normal salivary glands were extracted. Sections were prepared of these cases for Congo red staining. The malignant salivary gland tumors were classified as high-grade and low-grade malignancies. The slides were observed under ×10, and the highest-density areas were selected and counted in ten microscopic fields under ×40. Results: The density of the eosinophils was 4.5 ± 5.6 in the pleomorphic adenoma, 16.2 ± 6.01 in the low-grade MEC, 1.05 ± 1.1 in the high-grade MEC (Grade III), and the ACC, and 0.4 ± 0.89 in the normal salivary gland. Eosinophil density was significantly higher in low-grade malignancies compared to in benign or high-grade malignant neoplasms and normal salivary gland (P < 0.001). Conclusion: This is suggested which the density of eosinophils is associated with the process of tumorigenesis and the degree of malignancy in malignant salivary gland tumors.